The developmental regulator PatD modulates assembly of the cell‐division protein FtsZ in the cyanobacterium Anabaena sp. PCC 7120. (1st August 2021) - Wang, Li; Niu, Tian‐Cai; Valladares, Ana; Lin, Gui‐Ming; Zhang, Ju‐Yuan; Herrero, Antonia; Chen, Wen‐Li; Zhang, Cheng‐Cai
Summary: FtsZ is a tubulin‐like GTPase that polymerizes to initiate the process of cell division in bacteria. Heterocysts are terminally differentiated cells of filamentous cyanobacteria that have lost the capacity for cell division and in which the ftsZ gene is downregulated. However, mechanisms of FtsZ regulation during heterocyst differentiation have been scarcely investigated. The patD gene is NtcA dependent and involved in the optimization of heterocyst frequency in Anabaena sp. PCC 7120. Here, we report that the inactivation of patD caused the formation of multiple FtsZ‐rings in vegetative cells, cell enlargement, and the retention of peptidoglycan synthesis activity in heterocysts, whereas its ectopic expression resulted in aberrant FtsZ polymerization and cell division. PatD interacted with FtsZ, increased FtsZ precipitation in sedimentation assays, and promoted the formation of thick straight FtsZ bundles that differ from the toroidal aggregates formed by FtsZ alone. These results suggest that in the differentiating heterocysts, PatD interferes with the assembly of FtsZ. We propose that in Anabaena FtsZ is a bifunctional protein involved in both vegetative cell division and regulation of heterocyst differentiation. In the differentiating cells PatD‐FtsZ interactions appear to set an FtsZ activity that is insufficient for cell division but optimal to foster differentiation.